2017
DOI: 10.20524/aog.2017.0169
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and evaluation of prognostic factors after pancreaticoduodenectomy for distal cholangiocarcinoma

Abstract: BackgroundThe aim of the present study was to examine the outcomes and prognostic factors after surgery with curative intent for distal cholangiocarcinoma during a modern timespan, in a Swedish tertiary referral center.MethodsAll patients who underwent pancreaticoduodenectomy for distal cholangiocarcinoma between April 2008 and December 2015 were identified. Survival was estimated using the Kaplan-Meier analysis. Demographic, clinical, laboratory and histopathological data were evaluated for prognostic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
2
14
1
Order By: Relevance
“…Our study revealed a local recurrence rate of 11% after dCCA resection, which is lower than the previously reported rates of 14%–24% (12, 15). It is easier to achieve clear resection margins in patients with dCCA because, in contrast to pCCA, the anatomical structures around the tumor can usually be resected.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Our study revealed a local recurrence rate of 11% after dCCA resection, which is lower than the previously reported rates of 14%–24% (12, 15). It is easier to achieve clear resection margins in patients with dCCA because, in contrast to pCCA, the anatomical structures around the tumor can usually be resected.…”
Section: Discussioncontrasting
confidence: 84%
“…In several earlier studies, lymph node metastases were the most widely reported prognostic factor for dCCA (1216) and that tumor grade and CA19-9 levels were the most common prognostic factors for pCCA (17, 18). Although R0 resection is an important prognostic factor for pancreatic ductal adenocarcinoma, it appears to have a smaller role in CCA.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, the univariate analysis revealed a statistical significance of surgery-related prognostic factors such as vein resection, which had a statistically significant impact on the long-term survival and surgical complications on the short-term survival in the Kaplan-Meier analysis. This is in concordance with some previous studies, which described a worse prognosis for patients after portal vein resection 36,50,51 , while other studies did not find statistically significant results 1,52 . A limitation for the evaluation of additional vein resection is the small number of patients who could be included, which in our study was only 15.6% of all patients.…”
Section: Discussionsupporting
confidence: 93%
“…The 3-year survival rate of patients without lymph node metastasis was significantly higher than that of patients with lymph node metastasis (66.3% vs 36.1%, p < 0.001). Byrling et al [17] showed that lymph node metastasis was the only independent risk factor for long-term survival of patients with distal cholangiocarcinoma (R = 2.88, p = 0.016). Our research also showed that the long-term prognosis of patients without lymph node metastasis was better than that of patients with lymph node metastasis (p = 0.000).…”
Section: Discussionmentioning
confidence: 99%